Web-based Pentaca Sale Information System Implementation - Robo, Salahudin; Oktaviani, Alif Anas Tasya (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Pentaca products are experiencing problems in the form of managing Pentaca customer order data which is still being done manually by writing it in a book, making it difficult for Pencaca brand owners to manage customer data and make monthly reports for these products. The application of information systems in pentaca sales is needed to ensure that the business operates properly and improves the quality of service to customers. This study uses qualitative research methods to fulfill the use of the subject under study and collects data from various case studies, personal experiences, interviews with brand owners, visuals depicting everyday life. The system development uses the waterfall method. The data collection technique used is by direct observation, direct interviews and taking documentation of the business owner. With this system, it makes it easier for customers to buy these products and also makes it easier for brand owners to make monthly product purchase reports and manage financial reports.